Indicators of enrollment of students target audience of special education and the offer of multifunctional resource rooms in the state education network of Amazonas (Research, Society and Development, 2020)
This article analyzes the evolution of the school inclusion process of students targeting Special Education in relation to the enrollment and provision of multifunctional resource rooms in the Amazonas state network, in an attempt to follow the movement of policies and their intertwining with practices in schools. Secondary data from the Educational Censuses and the State Education Plan of Amazonas were used in the study, enrollments between 2008 and 2019 and the offer of multifunctional resource rooms in the years 2009 to 2019 in the state public school system of Amazonas -Brazil. In relation to the inclusion policy that has been implemented in the public school system of Amazonas, it  is  evident  that  the  number  of students  targeting  Special  Education  enrolled   in  the  years  has  increased  significantly; however,  when  analyzing  the  number  of  rooms  with  multifunctional  resources,  we  observed an insufficient growth to meet the demand.